2020
DOI: 10.1002/smll.201906048
|View full text |Cite
|
Sign up to set email alerts
|

Binary Chiral Nanoparticles Exhibit Amplified Optical Activity and Enhanced Refractive Index Sensitivity

Abstract: Metallic chiral nanoparticles (CNPs) with a nominal helical pitch (P) of sub‐10 nm contain inherent chirality and are promisingly applied to diverse prominent enantiomer‐related applications. However, the sub‐wavelength P physically results in weak optical activity (OA) to prohibit the development of these applications. Herein, a facile method to amplify the CNPs' OA by alloying the host CNPs with metals through a three‐step layer‐by‐layer glancing angle deposition (GLAD) method is devised. Promoted by the GLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…We have reported that the chirality can be effectively transferred from the host CNPs to the dopant M using the LbL‐GLAD, due to the diffusion of M into the chiral lattices of the host that is promoted by the GLAD‐induced heating effect. [ 38 ] The thermally diffused M atoms are spatially located in the chiral fashion duplicated from the chiral lattices of the host CNPs, i.e., the chiral alloying effect. The chiral alloying was observed in the binary Cu:Au nanostructures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported that the chirality can be effectively transferred from the host CNPs to the dopant M using the LbL‐GLAD, due to the diffusion of M into the chiral lattices of the host that is promoted by the GLAD‐induced heating effect. [ 38 ] The thermally diffused M atoms are spatially located in the chiral fashion duplicated from the chiral lattices of the host CNPs, i.e., the chiral alloying effect. The chiral alloying was observed in the binary Cu:Au nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…LbL-GLAD of Binary Cu:M CNPs (M: Au, Ag, TiO 2 ): Binary CNPs were generated through three-step LbL-GLAD processes. [38] The first and third step was the GLAD-FSR of the host unary Cu CNPs having a nominal P of roughly 10 nm and H of ≈50 nm, and the second step was the GLAD of dopant M without substrate rotation, with a nominal thickness of T M . M included Au (99.999%, Fuzhou Innovation Photoelectric Technology Co., LTD), Ag (99.99%, Kurt J. Lesker), and TiO 2 (99.9%, Kurt J. Lesker).…”
Section: Glad-fsr Of Unary Cnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…To extend the compositional space in Cu CNPs, Au with relatively high electrode potential was doped in the host using layer-by-layer GLAD (or LbL-GLAD) to generate the Cu:Au binary CNPs, where the GLAD heating effect caused the Au dopants to diffuse into the host chiral lattices and to duplicate the host's chirality. [54] The chiral Au functions as a structural scaffold to support the GRR-mediated chirality transfer, resulting in the generation of ternary Cu:Au:Pt and Cu:Au:Ag CNPs. [55] The composition and chiroplasmonic OA of polyelemental CNPs can be facilely adjusted as a function of the GRR duration.…”
Section: Nanoparticles With Chiral Atomic Latticesmentioning
confidence: 99%
“…[37] Chiral topographies at an atomic scale cause an enantiospecific interaction with molecules. [38,39] Furthermore, metal CNPs with chiral lattices have been extended in their compositional space from the unary to binary [40] and ternary, [41] and galvanic replacement reactions have been performed to produce porous binary CNPs. [42] These advanced developments make inorganic CNPs potentially function as asymmetric catalysts.…”
Section: Introductionmentioning
confidence: 99%